Resin composition, prepreg and laminated board
By using a combination of maleimide resin and DCPD cyanate in the laminate, combining flame retardant and filler, the heat resistance and processing performance of the laminate is optimized, and traditional epoxy resin is solved in the laminate The lack of performance in the application has achieved high-performance laminate preparation.
Patent Information
- Application Number
- CN202411406575.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional epoxy resins are difficult to meet the high requirements of heat resistance, mechanical properties, processability and dielectric properties in laminate applications, resulting in problems such as fast reactivity, narrow reaction windows, poor substrate quality and uneven plate thickness.
By defining the gelation time and number average molecular weight of the DCPD-type cyanate, the combination of flame retardant is combined with flame retardant by defining the gelation time and number average molecular weight of the DCPD-type cyanate. A resin composition with optimized processing performance is prepared by preparing a semi-cured sheet and laminate to optimize the comprehensive performance of the laminate.
The good heat resistance, HCT performance, peel strength and low dielectric properties of the laminate are achieved, and the problems of uncontrolled flow glue in the resin system and poor quality uniformity are solved, and the comprehensive performance of the laminate is optimized.
Smart Images

Figure BDA0005080404630000022 
Figure BDA0005080404630000033 
Figure BDA0005080404630000036
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electronic materials and relates to a resin composition, a prepreg and a laminate. Background Art
[0002] In recent years, with the development of the electronic information industry, the speed and volume of information processing have increased significantly. Terminals and base stations represented by 5G communications require faster signal transmission speeds and lower signal loss. Therefore, higher requirements are placed on the comprehensive performance of laminates (also known as copper clad laminates, CCLs).
[0003] Among them, printed circuit boards are constantly developing towards higher wiring density and higher integration. Traditional epoxy resins have been difficult to meet the high requirements of laminates in terms of heat resistance, mechanical properties, processability, dielectric properties, etc. Summary of the invention
[0004] The present application provides a resin composition, a prepreg, and a laminated board to solve the problems of poor heat resistance, mechanical properties, processability, and dielectric properties when epoxy resin is applied to laminated boards.
[0005] To achieve the above application purpose, one embodiment of the present application provides a resin composition, which comprises, by weight:
[0006] 10 to 40 parts by weight of maleimide resin or its modified prepolymer;
[0007] 5-20 parts by weight of epoxy resin;
[0008] 1 to 30 parts by weight of a first cyanate ester;
[0009] 5 to 30 parts by weight of the second cyanate;
[0010] 5 to 20 parts by weight of flame retardant;
[0011] 10 to 180 parts by weight of filler;
[0012] The first cyanate ester and the second cyanate ester are different from each other, the first cyanate ester is a DCPD type cyanate ester, and the gelation time of the DCPD type cyanate at 200° C. is 100 to 300 minutes.
[0013] As a further improvement of one embodiment of the present application, the gelation time of the DCPD-type cyanate ester is 130 to 230 minutes.
[0014] As a further improvement of one embodiment of the present application, the DCPD type cyanate ester is a prepolymer with a number average molecular weight of 200 to 3000.
[0015] As a further improvement of one embodiment of the present application, the number average molecular weight of the DCPD type cyanate ester is 200-1000.
[0016] As a further improvement of one embodiment of the present application, the structural formula of the DCPD type cyanate ester is
[0017] n is an integer from 1 to 10.
[0018] As a further improvement of one embodiment of the present application, the second cyanate ester is at least one of bisphenol A cyanate ester, bisphenol E cyanate ester, bisphenol F cyanate ester, bisphenol M cyanate ester, biphenyl cyanate ester, naphthalene cyanate ester, phenolic cyanate ester, tetramethyl bisphenol F cyanate ester, and a prepolymer of any of the above cyanates.
[0019] As a further improvement of an embodiment of the present application, the gelation time of the second cyanate ester is 70 to 150 minutes.
[0020] As a further improvement of one embodiment of the present application, the maleimide resin is at least one of the following structures:
[0021]
[0022] Structural formula (4), wherein R1 is methylene, ethylene or R2 is hydrogen, methyl or ethyl;
[0023]
[0024] n is an integer from 1 to 10;
[0025] n is an integer from 1 to 10;
[0026]
[0027] n is an integer from 1 to 10;
[0028] n is an integer from 1 to 10;
[0029] R is hydrogen, methyl or ethyl, and n is an integer of 1-10.
[0030] As a further improvement of one embodiment of the present application, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear phenolic epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.
[0031] As a further improvement of one embodiment of the present application, the epoxy resin is a dicyclopentadiene epoxy resin.
[0032] As a further improvement of one embodiment of the present application, the resin composition further comprises 0.01 to 5 parts by weight of a catalyst.
[0033] As a further improvement of one embodiment of the present application, the catalyst is selected from at least one of imidazole catalysts, pyridine catalysts, and organic metal salt catalysts.
[0034] As a further improvement of an embodiment of the present application, the catalyst is at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octanoate.
[0035] As a further improvement of one embodiment of the present application, the catalyst is a mixture of an imidazole catalyst and an organic metal salt catalyst in a mass ratio of 1: (0.5-5).
[0036] As a further improvement of one embodiment of the present application, the flame retardant is a bromine-based flame retardant, a phosphorus-based flame retardant, a nitrogen-based flame retardant or a silicon-based flame retardant.
[0037] As a further improvement of an embodiment of the present application, the brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide.
[0038] As a further improvement of one embodiment of the present application, the phosphorus-based flame retardant is selected from inorganic phosphorus, phosphate esters, phosphoric acid, hypophosphorous acid, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene or modified phosphazene.
[0039] As a further improvement of an embodiment of the present application, the filler is selected from at least one of an organic filler and an inorganic filler.
[0040] As a further improvement of an embodiment of the present application, the inorganic filler is selected from at least one of non-metallic oxides, metal nitrides, non-metallic nitrides, inorganic hydrates, inorganic salts, metal hydrates, and inorganic phosphorus.
[0041] As a further improvement of an embodiment of the present application, the inorganic filler is selected from at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talc, aluminum oxide, magnesium hydroxide, magnesium oxide, ceramic powder, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder. The silicon dioxide includes fused silica, crystalline silica, spherical silica, and hollow silica.
[0042] As a further improvement of an embodiment of the present application, the inorganic filler is at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talcum powder, aluminum oxide, magnesium hydroxide, magnesium oxide, and ceramic powder.
[0043] As a further improvement of an embodiment of the present application, the inorganic filler is silicon dioxide.
[0044] As a further improvement of an embodiment of the present application, the inorganic filler is spherical silica that has been surface treated.
[0045] As a further improvement of an embodiment of the present application, the organic filler is selected from at least one of polytetrafluoroethylene powder, polyphenylene sulfide, and polyethersulfone powder.
[0046] As a further improvement of an embodiment of the present application, the filler is pre-surface treated with a silane coupling agent, and the silane coupling agent is a silane coupling agent containing an epoxy group, an amino group, a vinyl group, an acrylate group or an allyl group.
[0047] As a further improvement of an embodiment of the present application, the median particle size of the filler is 1 to 15 microns.
[0048] The present application also provides a prepreg, comprising a reinforcing material and the aforementioned resin composition; the resin composition is attached to the reinforcing material.
[0049] The preparation method of the prepreg comprises:
[0050] Dissolving the resin composition with a solvent to prepare a glue solution;
[0051] The reinforcing material is immersed in the above-mentioned glue solution, and the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.
[0052] As a further improvement of one embodiment of the present application, the solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.
[0053] As a further improvement of an embodiment of the present application, the reinforcing material is selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.
[0054] The present application also provides a laminate, comprising a metal foil and the aforementioned prepreg; the metal foil is arranged on at least one side surface of the prepreg or a combination of a plurality of the prepregs.
[0055] The preparation method of the laminate is: a metal foil is coated on one side or both sides of a prepreg, or at least two prepregs are stacked to form a combined sheet, a metal foil is coated on one side or both sides of the combined sheet, and a metal foil laminate is obtained by hot pressing. The pressing conditions of the hot pressing are: a pressure of 0.2 to 2 MPa, a temperature of 150 to 250° C., and a pressing time of 2 to 4 hours.
[0056] Due to the application of the above technical solution, the present application has the following beneficial effects compared with the prior art: by adopting DCPD-type cyanate ester and other types of cyanate esters, and limiting the gelation time of DCPD-type cyanate ester, the problem of too fast reactivity and narrow reaction window of maleimide resin or its modified prepolymer with cyanate ester curing system can be solved, and when applied to copper-clad laminates and PCB boards, the processing performance of copper-clad laminates and PCB boards is optimized; the laminate prepared based on the resin composition has good heat resistance, HCT performance, peel strength, low dielectric performance, good comprehensive performance, and optimizes the problems of uncontrolled glue flow of the resin system, poor substrate quality and plate thickness uniformity. DETAILED DESCRIPTION
[0057] The technical solution of the present application is further introduced below in conjunction with specific implementation methods. The following embodiments are merely descriptive and not restrictive, and the protection scope of the present application cannot be limited by them.
[0058] One embodiment of the present application provides a resin composition and a prepreg, a laminate, an insulating board, an insulating film, a circuit substrate and an electronic device made using the resin composition, that is, the resin composition in a prepreg, a laminate.
[0059] First, the present application provides a resin composition, which comprises, by weight:
[0060] 10 to 40 parts by weight of maleimide resin or its modified prepolymer;
[0061] 5-20 parts by weight of epoxy resin;
[0062] 1 to 30 parts by weight of a first cyanate ester;
[0063] 5 to 30 parts by weight of the second cyanate;
[0064] 5 to 20 parts by weight of flame retardant;
[0065] 10 to 180 parts by weight of filler;
[0066] The first cyanate ester and the second cyanate ester are different from each other, the first cyanate ester is a DCPD type cyanate ester, and the gelation time of the DCPD type cyanate at 200° C. is 100 to 300 minutes.
[0067] By adopting DCPD cyanate ester and other types of cyanate esters and limiting the gelation time of DCPD cyanate ester, the problems of too fast reactivity of maleimide resin or its modified prepolymer with cyanate ester curing system, narrow reaction window, substrate drying and uneven thickness can be solved, and when applied to copper clad laminates and PCB boards, the processing performance of copper clad laminates and PCB boards is optimized; the laminate prepared based on the resin composition has good heat resistance, HCT performance, peel strength, low dielectric performance, good comprehensive performance, and optimizes the problems of uncontrolled glue flow of the resin system, poor substrate quality and plate thickness uniformity.
[0068] When the gelation time of DCPD cyanate ester resin is less than 100 minutes, its self-curing reaction and the reaction with maleimide resin or its modified prepolymer are too fast. When the gelation time of DCPD cyanate ester resin is more than 300 minutes, the reaction is too slow, and it is easy to cause processing problems such as excessive glue flow and sliding during the lamination process.
[0069] Preferably, the gelation time of the DCPD-type cyanate ester is 130 to 230 minutes.
[0070] Preferably, the DCPD type cyanate ester is a prepolymer with a number average molecular weight of 200 to 3000.
[0071] By limiting the gelation time and number average molecular weight of the DCPD cyanate ester resin, the self-curing reaction of the DCPD cyanate ester resin in the maleimide resin system and the reaction with the maleimide group can be controlled, thereby solving the problem of poor substrate quality caused by too fast curing reaction in the system.
[0072] More preferably, the number average molecular weight of the DCPD type cyanate ester is 200-1000.
[0073] The structural formula of the DCPD type cyanate ester is
[0074] n is an integer from 1 to 10.
[0075] The second cyanate is at least one of bisphenol A cyanate, bisphenol E cyanate, bisphenol F cyanate, bisphenol M cyanate, biphenyl cyanate, naphthalene cyanate, phenolic cyanate, tetramethyl bisphenol F cyanate, and prepolymers of any of the above cyanates. That is, the second cyanate is at least one of bisphenol A cyanate, bisphenol E cyanate, bisphenol F cyanate, bisphenol M cyanate, biphenyl cyanate, naphthalene cyanate, phenolic cyanate, tetramethyl bisphenol F cyanate, and prepolymers of bisphenol A cyanate, prepolymers of bisphenol E cyanate, prepolymers of bisphenol F cyanate, prepolymers of bisphenol M cyanate, biphenyl cyanate, prepolymers of naphthalene cyanate, prepolymers of phenolic cyanate, and prepolymers of tetramethyl bisphenol F cyanate.
[0076] Preferably, the gelation time of the second cyanate ester is 70 to 150 minutes.
[0077] The maleimide resin is at least one of the following structures:
[0078]
[0079] Wherein, R1 is methylene, ethylene or R2 is hydrogen, methyl or ethyl;
[0080]
[0081] n is an integer from 1 to 10;
[0082] n is an integer from 1 to 10;
[0083]
[0084] n is an integer from 1 to 10;
[0085] n is an integer from 1 to 10;
[0086] R is hydrogen, methyl or ethyl, and n is an integer of 1-10.
[0087] The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear phenolic epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.
[0088] The epoxy resin is preferably a dicyclopentadiene epoxy resin.
[0089] Furthermore, the resin composition further comprises 0.01 to 5 parts by weight of a catalyst.
[0090] The catalyst is selected from at least one of imidazole catalysts, pyridine catalysts and organic metal salt catalysts.
[0091] Preferably, the catalyst is at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octoate.
[0092] More preferably, the catalyst is an imidazole catalyst and an organic metal salt catalyst according to 1:
[0093] A mixture of the following:
[0094] The flame retardant is a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant or a silicon flame retardant.
[0095] The brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide.
[0096] The phosphorus flame retardant is selected from inorganic phosphorus, phosphate ester, phosphoric acid, hypophosphorous acid, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene or modified phosphazene.
[0097] The filler is selected from at least one of an organic filler and an inorganic filler.
[0098] The inorganic filler is selected from at least one of non-metallic oxides, metal nitrides, non-metallic nitrides, inorganic hydrates, inorganic salts, metal hydrates, and inorganic phosphorus.
[0099] Preferably, the inorganic filler is selected from at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talc, aluminum oxide, magnesium hydroxide, magnesium oxide, ceramic powder, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder. More preferably, the inorganic filler is at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talc, aluminum oxide, magnesium hydroxide, magnesium oxide, and ceramic powder.
[0100] The silica includes fused silica, crystalline silica, spherical silica and hollow silica.
[0101] The inorganic filler is more preferably silicon dioxide, especially surface-treated spherical silicon dioxide.
[0102] The organic filler is selected from at least one of polytetrafluoroethylene powder, polyphenylene sulfide and polyethersulfone powder.
[0103] Furthermore, the filler is pre-surface treated with a silane coupling agent, and the silane coupling agent is a silane coupling agent containing an epoxy group, an amino group, a vinyl group, an acrylate group or an allyl group.
[0104] Preferably, the median particle size of the filler is 1 to 15 microns, specifically 1 micron, 2 microns, 5 microns, 8 microns, 10 microns, 11 microns, 12 microns, 13 microns, or 14 microns.
[0105] More preferably, the median particle size of the filler is 1 to 10 microns.
[0106] The present application also provides a prepreg, comprising a reinforcing material and the aforementioned resin composition; the resin composition is attached to the reinforcing material.
[0107] The preparation method of the prepreg comprises:
[0108] Dissolving the resin composition with a solvent to prepare a glue solution;
[0109] The reinforcing material is immersed in the above-mentioned glue solution, and the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.
[0110] In a specific embodiment, the method for preparing the prepreg comprises:
[0111] Dissolving the resin composition with a solvent to prepare a glue solution;
[0112] The reinforcing material is immersed in the above-mentioned glue solution, and the immersed reinforcing material is baked at 100° C. to 180° C. for 1 to 15 minutes. After drying, the prepreg sheet can be obtained.
[0113] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.
[0114] The reinforcing material is selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics, preferably glass fiber cloth, more preferably E glass fiber cloth, S glass fiber cloth, T glass fiber cloth, or Q glass fiber cloth. The glass fiber cloth is preferably open fiber cloth or flat cloth.
[0115] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth is chemically treated with a coupling agent in advance to improve the interface bonding between the resin composition and the glass fiber cloth. The coupling agent is preferably an epoxy silane coupling agent or an amino silane coupling agent to make the reinforcing material have good water resistance and heat resistance.
[0116] The present application also provides a laminate, comprising a metal foil and the aforementioned prepreg; the metal foil is arranged on at least one side surface of the prepreg or a combination of a plurality of the prepregs.
[0117] In a specific embodiment, the laminate includes a piece of the aforementioned prepreg and a metal disposed on at least one side of the prepreg.
[0118] In another specific implementation, the laminate includes a composite sheet formed by overlapping a plurality of the aforementioned prepreg sheets and a metal foil disposed on at least one side of the composite sheet.
[0119] The preparation method of the laminate is: a metal foil is coated on one side or both sides of a prepreg, or at least two prepregs are stacked to form a composite sheet, a metal foil is coated on one side or both sides of the composite sheet, and a metal foil laminate is obtained by hot pressing. The pressing conditions of the hot pressing are: a pressure of 0.2 to 2 MPa, a temperature of 150 to 250°C, and a pressing time of 2 to 4 hours. The metal foil is selected from copper foil or aluminum foil, and the thickness is 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.
[0120] The technical solution of the present application is further described below in conjunction with some specific embodiments and comparative examples. Of course, these embodiments are only a part of the many variations of the embodiments of the present application, but not all.
[0121] The chemical components and contents of the resin compositions of Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] Among them, GT is the gelation time; the second cyanate ester is bisphenol A cyanate, and its gelation time GT = 100min; the flame retardant is The filler is silicon dioxide.
[0126] The above examples and comparative examples also prepare a prepreg, comprising glass fiber cloth as a reinforcing material and a resin composition attached to the glass fiber cloth by an impregnation method, wherein the glass fiber cloth is ordinary electronic grade 2116 glass fiber cloth.
[0127] Specifically, the components of the resin compositions of Examples 1 to 4 and Comparative Examples 1 to 3 in Table 1 were dissolved in butanone, stirred and mixed, and then diluted to a glue solution with a solid content of 60 wt %; the glass fiber cloth was immersed in the glue solution for 5 min, then taken out, placed in a blast drying oven at 170° C., and baked for 3 to 6 min to obtain a semi-cured sheet.
[0128] The above embodiments and comparative examples also prepare a laminated board, which is prepared by the following method:
[0129] Take 6 pieces of the above-mentioned semi-cured sheets, cut them into 300×300mm, and stack them into a certain stacking structure. Then, place a low-profile electrolytic copper foil with a thickness of 18μm on both sides of the combined sheet, place them in a vacuum hot press, and hot press them for 2.5h at a pressure of 1.5MPa and a high temperature section temperature of 220℃ to obtain a copper-clad laminate with a thickness of 0.6mm.
[0130] The copper-clad laminates obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to performance testing, and the test results are shown in Table 2. The performance testing method includes:
[0131] (1) Glass transition temperature (Tg): The DMA (thermomechanical analysis) method was used to test the dynamic mechanical properties of the steel using a dynamic mechanical properties tester (TA DMA Q800, USA) in accordance with the method specified in IPC-TM-6502.4.25. The heating rate was 10°C / min and the atmosphere was nitrogen.
[0132] (2) Dk and Df: The dielectric constant Dk and dielectric loss Df at 10 GHz were measured using the plate method in accordance with IPC-TM-650 2.5.5.9.
[0133] (3) Peel strength (PS): The peel strength of the copper foil layer of the laminate was tested according to the "after thermal stress" experimental conditions in IPC-TM-650 2.4.8 method.
[0134] (4) Tin immersion heat resistance (s): A 50×50 mm double-sided copper foil sample was used and immersed in 288°C solder. The time for the sample to delaminate and bubble was recorded.
[0135] (5) HCT performance: HCT reliability test, to check the durability performance under different temperature conditions, the test conditions are: room temperature is 20±15℃, test for 20s; hot oil temperature is 260±5℃, test for 20s; 46 cycles, resistance is measured once in each cycle, and it is qualified when (maximum resistance value of hot oil test - minimum resistance value of hot oil test) / minimum resistance value of hot oil test < 100%.
[0136] (6) Water absorption: The water absorption rate was measured according to the method of IPC-TM-6502.6.2.1. Specifically, three samples with a length × width of 10 cm × 10 cm and a thickness of 0.8 mm were taken, and the electrolytic copper foil on both sides was removed. The samples were dried at 120°C for 2 h and weighed. The weight was recorded as W1. The samples were then treated in a pressure cooker at 121°C and 2 atmospheres for 7 h. After the free water on the surface was absorbed, the samples were placed in a desiccator and cooled. The weight was recorded as W2. The water absorption rate was measured as (W2-W1) / W1×100%.
[0137] (7) X / Y thermal expansion coefficient (CTE): TMA (thermomechanical analysis) was used with a heating rate of 10°C / min and a test temperature range of 30 to 100°C.
[0138] (8) Sub-apparent quality: Visually inspect the appearance of the CCL substrate. A substrate without obvious glue deficiency or pinholes is judged as having good appearance. A substrate with glue deficiency or pinholes is judged as having fair appearance.
[0139] Table 2
[0140]
[0141]
[0142] Among them, the heat resistance and HCT performance of comparative example 1 are poor, the base material has large glue flow, the thickness range is large, the uniformity of the board is poor, and the board is prone to incomplete curing and poor processability; the curing time of the board of comparative example 2 is too fast, the resin is not easy to flow, the board is prone to dry flowers and voids, the pressed board has poor heat resistance and HCT performance, and poor processability; the board of comparative example 3 has poor heat resistance.
[0143] The resin composition of the embodiment of the present application has high moisture and heat resistance, HCT performance, peel strength, and low dielectric properties, while improving the poor appearance and thickness of the semi-cured sheet and the substrate, and has good processability.
[0144] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0145] The detailed descriptions listed above are merely specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A resin composition, characterized in that By weight, including: 10 to 40 parts by weight of maleimide resin or its modified prepolymer; 5-20 parts by weight of epoxy resin; 1 to 30 parts by weight of a first cyanate ester; 5 to 30 parts by weight of the second cyanate; 5 to 20 parts by weight of flame retardant; 10 to 180 parts by weight of filler; The first cyanate ester and the second cyanate ester are different from each other, the first cyanate ester is a DCPD type cyanate ester, and the gelation time of the DCPD type cyanate at 200° C. is 100 to 300 minutes.
2. The resin composition according to claim 1, characterized in that The DCPD type cyanate ester is a prepolymer with a number average molecular weight of 200 to 3000.
3. The resin composition according to claim 2, characterized in that The structural formula of the DCPD type cyanate ester is n is an integer from 1 to 10.
4. The resin composition according to claim 1, characterized in that The second cyanate ester is at least one of bisphenol A cyanate ester, bisphenol E cyanate ester, bisphenol F cyanate ester, bisphenol M cyanate ester, biphenyl cyanate ester, naphthalene cyanate ester, phenol formaldehyde cyanate ester, tetramethyl bisphenol F cyanate ester, and prepolymers of any of the above cyanate esters.
5. The resin composition according to claim 1, characterized in that The maleimide resin is at least one of the following structures: Wherein, R1 is methylene, ethylene or R2 is hydrogen, methyl or ethyl; n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; R is hydrogen, methyl or ethyl, and n is an integer of 1-10.
6. The resin composition according to claim 1, characterized in that The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear phenolic epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.
7. The resin composition according to claim 1, characterized in that The flame retardant is a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant or a silicon flame retardant.
8. The resin composition according to claim 1, characterized in that The filler is at least one of silicon dioxide, aluminum hydroxide, talcum powder, aluminum oxide, magnesium hydroxide, magnesium oxide, and ceramic powder.
9. A prepreg, comprising a reinforcing material and the resin composition according to any one of claims 1 to 8; the resin composition is attached to the reinforcing material.
10. A laminated board, characterized in that: It comprises a metal foil and the prepreg as claimed in claim 9; the metal foil is arranged on at least one side surface of the prepreg or a combination of a plurality of the prepregs.
